Stabilized IMC-PI controller designing for IPDT processes based on gain and phage margin criteria. (2020) - Nath, Ujjwal Manikya; Dey, Chanchal; Mudi, Rajani K.
Abstract: Objective of this work is to design proportional integral (PI) controller based on internal model control (IMC) approach. Proportional ( kc ) and integral ( kI ) gains of the proposed IMC-PI controller for integrating plus dead time (IPDT) processes are calculated based on gain and phase margin specifications. Suitable choice of the sole tuning parameter for IMC-PI controller i.e. closed loop time constant (λ) plays crucial towards achieving the desired closed loop response. Comprehensible guideline is provided here towards appropriate choice of (λ). Efficacy of the proposed scheme is verified through simulation study on IPDT processes during servo as well as regulatory responses in comparison with other reported settings.